Localness in Luxury Fashion on the Example of Brunello Cucinelli - Michalíčková, Růžena (2023)
The objective of the thesis is to determine whether the factor of brand’s localness in the luxury fashion industry can be the brand’s key asset when expanding outside of the home market. To answer the question, the thesis focuses on Brunello Cucinelli, an Italian luxury fashion brand, strongly connected to its roots since its foundation.